Implementation Of Social Function With Qardh Contract At Bank Devisa Syariah In Indonesia - Mohamad Torik Langlang Buana; Sofyan Halim (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
The aim of this research is to check and find out the implementation of social function from foreign-activity (devisa) sharia banking in Indonesia. The research method is using observation by analyzing the yearly financial reports, information stated in notes to the accounts, the research also using interview with front end staffs in some foreign-activity sharia banking, the interviews were also held with communication with call center’s from those banks. The technique of collecting data for this research is field research with relating the reference to the principles. Using direct interview with non-structured interview. Analyzing the data were held qualitatively and presented in descriptive manners. Based on the research, it took the conclusions, that the application of qardh lending in foreign-activity sharia banking is not applicable to ordinary customers. In some foreign-activity (devisa) sharia banks, there are exist qardh loan application with some prequisities such gold as collateral, through credit cards facility with blocking balance of funds in savings account. The research concludes that the social financing is not available for ordinary customers, even the reports showing the increment the value in the year of 2015, 2016 and 2017